Normalized Shear Modulus and Damping Ratio of Soil–Rock Mixtures With Different Volumetric Block Proportions - Wang, Shengnian; Gao, Xinqun; Hui, Honglei; Ma, Wei; Shi, Chong; Zhang, Peng (Frontiers in Physics, 2021)
The volume fraction of rock blocks plays a particularly significant role in static/dynamic shear behaviors of soil-rock mixtures (SRM). Large-scale cyclic triaxial tests for SRM with different volumetric block proportions (VBP) were performed at different confining pressures to investigate the reduction of dynamic shear modulus (G) and the increase of damping ratio (λ). Results indicate that VBP has a significant effect on the dynamic behaviors of SRM. The higher VBP is more likely to result in a gentler reduction of G and a faster increase of λ. The variations of dynamic shear modulus ratio (G/G0) and normalized damping ratio (λnor) fall within relatively narrow bands but are very different with gravelly soils and sands due to VBP with particle size larger than 2mm. The G/G0 and λnor can be characterized by empirical functions about normalized shear strain amplitude (γnor).